1998
DOI: 10.2739/kurumemedj.45.333
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of the Branching of the Human Internal Iliac Artery.

Abstract: This study is based on the dissections of 645 pelvic halves of Japanese cadavers. The branching of the internal iliac artery was classified according to Adachi's classification (1928) , and the data was compared with previous reports. Type I was predominant in this , as well as, in previous studies. During the course of the present study, some branching forms were different from the types in Adachi's classification. Therefore, this classification was modified into 5 types and 19 groups. Type I-Group 1 was most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 3 publications
4
70
1
1
Order By: Relevance
“…So for a successful ligation of the IIA, the operating surgeon should be cognizant of the level of origin, the level of division of the artery; unilateral or bilateral ligation of the IIA can be lifesaving in patients with massive postpartum hemorrhage, after vaginal and abdominal hysterectomy; in massive broad ligament hematoma, cervical carcinoma, and retroperitoneal bleeding after pelvic fractures, bilateral IIA ligation is done. In the present study, in 40 % specimens, variant branches were observed [6][7][8].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…So for a successful ligation of the IIA, the operating surgeon should be cognizant of the level of origin, the level of division of the artery; unilateral or bilateral ligation of the IIA can be lifesaving in patients with massive postpartum hemorrhage, after vaginal and abdominal hysterectomy; in massive broad ligament hematoma, cervical carcinoma, and retroperitoneal bleeding after pelvic fractures, bilateral IIA ligation is done. In the present study, in 40 % specimens, variant branches were observed [6][7][8].…”
Section: Discussionmentioning
confidence: 91%
“…Yamaki et al [8], in their study based on the dissection of 645 pelvic halves of Japanese cadavers, the branching of the IIA was classified into four groups. In almost 80 % of the specimens, the IIA is dividing into two major branches, the superior gluteal artery and the common trunk for the inferior gluteal and internal pudendal arteries [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives rise to the visceral branches (uterine artery, superior and inferior vesical arteries, middle and inferior rectal arteries) and the parietal branches (ilio-lumbar artery, lateral sacral artery, superior and inferior gluteal arteries, obturator artery and internal pudendal artery) [37,38] (Figs. 2 and 3).…”
Section: Computed Tomography Injury Assessment: What the Radiologist mentioning
confidence: 99%
“…Few studies have addressed radiologically the anatomy of the male pelvic arterial system (14,15) and PAs (16). Knowledge of the male pelvic and PA anatomy is needed to safely perform PAE.…”
mentioning
confidence: 99%